Microclima sob a copa do mamoeiro, ao longo do ano, e cultivando com café e em diferentes orientações de plantio - Trevisan, Evelyn (2017)
The Conilon coffee is a species originally adapted to partially shaded environments, however, in Brazil, its cultivation is carried out in full sun. During the critical stage of grain filling, coffee is often subjected to high temperatures, which can cause crop stress, requiring different techniques to mitigate these problems. Thus, shading appears as a technique for mitigating climatic variables. In this context, two works were developed: the first one was to evaluate the microclimate and the development of the coffee Conilon, in a system of coffee cultivation consorciado with papaya. The papaya tree was planted at 3,20x2,40m spacing, in July 2014, and the coffee was planted at 3,20x1,60m spacing in March 2015, in the papaya line. The distances of the coffee and papaya line (40 and 80cm north and south) and full sun in the north and south orientation were considered as treatments. It was evaluated the atmospheric variables (temperature, irradiance, relative humidity), leaf area and relative index of chlorophyll, length of the plagiotropic, orthotropic and number of nodes, in three seasons of the year. The consortium of the Conilon coffee plant with Mamoeiro provided a decrease in irradiance and temperature, and higher values of relative air humidity during the day in all evaluated periods. The shading provided greater leaf expansion, however did not influence the growth of plagiotropic and orthotropic branches and the number of nodes. The system of consortium of the coffee plant Conilon with papaya under the conditions studied presented potential. The second one had the objective to evaluate the variations of the environmental factors under the canopy of papaya, planted in the sense of North-South and East-West orientation. Two areas of papaya, one planted in the North-South orientation and the other EastWest, were planted at a spacing of 3.20x2.40m, both planted in April 2015. The treatments were considered the distances of the papaya line, and one In the northsouth direction: at the planting line of the papaya (T1), at 40cm west side (T2 O), viii 40cm east side (T3 L) and at full sun (T4 Sol) ; In the East-West direction: in the planting line of the papaya (T1), at 40cm north side (T2 N), 40cm South side (T3 S) and in the planting line at full sun (T4 Sun). Atmospheric variables (temperature, irradiance, relative humidity) were evaluated. The papaya planted in the east-west direction, under the conditions studied, provided less incident radiation, reduction in temperature and higher values of relative humidity of the air under its canopy. According to the microclimatic conditions presented, the consortium of papaya planted in both directions becomes possible.